Physiological consequences of rising water salinity for a declining freshwater turtle. Issue 1 (21st August 2019) - Agha, Mickey; Yanagitsuru, Yuzo R; Fangue, Nann A; Nowakowski, A Justin; Kojima, Laura V; Cech, Joseph J; Riley, Melissa K; Freeman, Janna; Cocherell, Dennis E; Todd, Brian D
Abstract : Two populations of a declining western North American freshwater turtle—one coastal and one inland—were exposed to elevated water salinities of 10 ppt and 15 ppt over 2 weeks. Turtles from the coastal estuarine population had reduced feeding and drinking and maintained lower plasma osmolality levels than did those from inland. Abstract: Sea-level rise, drought and water diversion can all lead to rapid salinization of freshwater habitats, especially in coastal areas. Increased water salinities can in turn alter the geographic distribution and ecology of freshwater species including turtles. The physiological consequences of salinization for freshwater turtles, however, are poorly known. Here, we compared the osmoregulatory response of two geographically separate populations of the freshwater Western Pond Turtle ( Actinemys marmorata )—a species declining across its range in western North America—to three constant salinities: 0.4 ppt, 10 ppt and 15 ppt over 2 weeks. We found that turtles from a coastal estuarine marsh population regulated their plasma osmolality at lower levels than their conspecifics from an inland freshwater creek population 45 km away. Plasma osmolalities were consistently lower in estuarine marsh turtles than the freshwater creek turtles over the entire 2-week exposure to 10 ppt and 15 ppt water. Furthermore, estuarine marsh turtles maintained plasma osmolalities within 1 SD of their mean field osmolalities over the 2-week exposure, whereas freshwater creek turtles exceeded their field values within the first few days after exposure to elevated salinities. However, individuals from both populations exhibited body mass loss in 15 ppt water, with significantly greater loss in estuarine turtles. We speculate that the greater ability to osmoregulate by the estuarine marsh turtles may be explained by their reduced feeding and drinking in elevated salinities that was not exhibited by the freshwater creek population. However, due to mass loss in both populations, physiological and behavioural responses exhibited by estuarine marsh turtles may only be effective adaptations for short-term exposures to elevated salinities, such as those from tides and when traversing saline habitats, and are unlikely to be effective for long-term exposure to elevated salinity as is expected under sea-level rise.